MATHEMATICAL MODELING AND HYSTERESIS OF SORPTION ISOTHERMS FOR PADDY RICE GRAINS - Zeymer,Juliana S. (2019)
ABSTRACT Knowledge on sorption isotherms is important for predicting drying and storage processes of a product. A sorption isotherm can be generated from two processes: desorption and adsorption. The lag between these two curves is called hysteresis. Static method was used to obtain the equilibrium moisture content of paddy rice grains, in different temperature (10, 20, 30, 40 and 50 ± 1°C) and relative humidity (between 11 and 76% ± 2%) conditions. Equilibrium moisture content data were correlated with eight mathematical models and. The Chung Pfost model had the best fit to the experimental data. Desorption and adsorption isotherms, represented by the Chung Pfost model, showed a sigmoidal shape, characteristic of type II curve. Equilibrium moisture content values obtained by desorption were higher than those obtained by adsorption, evidencing the hysteresis phenomenon.